Nonalcoholic Fatty Liver Disease in Patients with Psoriasis - Fatema, Kaneez; Helal, ASM Julfekar (Community Based Medical Journal, 2026)
Psoriasis is a chronic inflammatory skin disease associated with an increased risk for non-alcoholic fatty liver disease (NAFLD) compared with general population. Chronic low-grade inflammation in psoriasis plays role in the development of NAFLD. However, there is scarcity of studies reporting on the systematic evaluations of the prevalence of NAFLD in patients with psoriasis disorder. This cross-sectional, comparative study was conducted in the Department of Dermatology and Venereology, Dhaka Medical College Hospital, Bangladesh, from September 2019 to August 2020, to observe association between NAFLD and psoriasis. A total of 50 patients with psoriasis were selected as case group and another 50, age and sex matched participants were selected as control group according to selection criteria. Informed written consent was taken from each patient. Detail history was taken; thorough physical examination and relevant investigations were done. All information’s were recorded in a separate case record form. Most of psoriasis patients were in 36-50 years (36%) group with a mean age of 40.74±11.61 years. Male dominance was found in psoriatic patient (74%). Prevalence of NAFLD was significantly higher in psoriatic patient than in control (70% vs 26%; p<.05). Among the patients with NAFLD 18% had Grade I, 20% had Grade II, 10% had Grade III. Among psoriasis patient 14% had mild, 56% had moderate and 30% had severe psoriasis according to psoriasis area and severity index (PASI). While increasing PASI score, the stage of fibro scan of liver also increased. The association of PASI and steatosis grade of fatty liver stage was found significant (p<0.001). The study revealed that NAFLD was very frequent among patients having psoriasis (70%) and a statistically significant association was observed between the severity of NAFLD and psoriasis. However, further studies with lager samples are recommended. CBMJ 2026 January: vol. 15 no. 01 P:26-34